2016
DOI: 10.3892/etm.2016.3116
|View full text |Cite
|
Sign up to set email alerts
|

Allicin inhibits transient outward potassium currents in mouse ventricular myocytes

Abstract: Abstract. Allicin is the active constituent of garlic, a widely used spice and food. The remedial properties of garlic have also been extensively researched and it has been demonstrated that allicin is able to inhibit the transient outward potassium current (I to ) in atrial myocytes. However, the direct effect of allicin on I to in ventricular myocytes has yet to be elucidated. In the present study, the effects of allicin on I to in ventricular myocytes isolated from mice were investigated, using the whole-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…As previously explained, the former mechanism is likened to the action of I K 1 agonists in subclass III b AADs ( 7 ). One other mechanistic study found the inhibitory effects of allicin on I to in isolated ventricular myocytes similar to the action of subclass IIIa; however, this study has not evaluated the arrhythmia outcomes ( 61 ), and this issue should be clarified in future studies.…”
Section: Resultsmentioning
confidence: 92%
“…As previously explained, the former mechanism is likened to the action of I K 1 agonists in subclass III b AADs ( 7 ). One other mechanistic study found the inhibitory effects of allicin on I to in isolated ventricular myocytes similar to the action of subclass IIIa; however, this study has not evaluated the arrhythmia outcomes ( 61 ), and this issue should be clarified in future studies.…”
Section: Resultsmentioning
confidence: 92%
“…In line with this study, in mouse ventricular myocytes, allicin gradually inhibited the transient outward potassium currents (I to ) in a dose-dependent fashion. Furthermore, the high concentration of allicin accelerated the voltage-dependent inactivation of I to , which produced a significant effect on negative potential and cardiac repolarization [ 104 ]. In the primary cell culture of cardiomyocytes, allicin inhibited the translocation of the l-type calcium (Cav1.2) channel, from the endoplasmic reticulum to the cell membrane.…”
Section: Effects Of Allicin On Cardiovascular Risk Factorsmentioning
confidence: 99%
“…Una propiedad de la alicina que apoya su utilidad en las ECV son sus efectos antiarrítmicos y esto se demostró en ensayos in vitro analizando sus efectos sobre canales iónicos y sobre la duración del potencial de acción. En miocitos ventriculares aislados, la alicina inhibió la corriente transitoria de potasio hacia el medio extracelular (exterior) en forma dependiente de la dosis 56 . En cultivo celular primario de cardiomiocitos la alicina inhibió la translocación del canal de calcio tipo L del retículo endoplásmico a la membrana celular.…”
Section: Arritmiaunclassified